2007
DOI: 10.1063/1.2813786
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Photoproduction of Pseudoscalar Mesons at Forward Angles up to 6.0 GeV

Abstract: Abstract. The nuclear incoherent 71" photoproduction cross section from '^C is evaluated at forward angles in the 4.0 to 6.0 GeV energy range using the multicoUisional intranuclear cascade model MCMC. The model incorporates some improvements in comparison with previous versions associated with the momentum distribution (MD) for light nuclei -extracted from the available (e,e'p) data -as well as the evaluation of the shadowing effects during the photonucleus interaction. The final results of the single and doub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…2 from Ref. [45]), leading to a systematic uncertainty in the decay width of less than 2% for the combined fit (Be and Cu) and less than 4% for the single fit (Be only).…”
Section: Extracting the η → γ γ Decay Width Via The Primakoff Methodmentioning
confidence: 99%
See 1 more Smart Citation
“…2 from Ref. [45]), leading to a systematic uncertainty in the decay width of less than 2% for the combined fit (Be and Cu) and less than 4% for the single fit (Be only).…”
Section: Extracting the η → γ γ Decay Width Via The Primakoff Methodmentioning
confidence: 99%
“…We have also investigated the sensitivity of the cascade results using empirical (distorted) momentum distributions from several nucleon knock-out experiments (see Table 1 from Ref. [45]). An extensive review of the proton knock-out data for light nuclei can be found in Ref.…”
mentioning
confidence: 99%